Preparation method and application of Se defect-rich iron diselenide / ferroferric oxide heterostructure

The preparation of the heterostructure catalyst of iron diselenide/ferrotetraoxide rich in Se defects was solved by hydrothermal method, which solved the problem of low nitrate conversion efficiency in neutral environments, achieved high selectivity and high activity catalytic effects, and was suitable for electrocatalytic nitrate reduction reactions.

CN119608189APending Publication Date: 2025-03-14QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411491966.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to convert nitrates quickly and efficiently in neutral environments, and lacks high selectivity and high activity catalysts, limiting the efficiency of nitrate reduction reactions.

Method used

The iron diselenide/ferrotetraoxide heterostructure (FeSe2-x/Fe3O4) rich in Se defects was prepared by a one-step hydrothermal method. Selenium powder and iron salt were used as raw materials, and sodium borohydride was used as phase conversion and Se defect formation inducer to prepare a catalyst with a nanocube structure and nanoparticle surface.

Benefits of technology

The catalyst exhibits high activity and selectivity in neutral solution, can significantly improve the ammonia yield and selectivity of nitrate reduction reaction under -1.2V vs. RHE conditions, and has good cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608189A_ABST
    Figure CN119608189A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of an iron diselenide / ferroferric oxide heterostructure rich in Se defect, selenium powder and sodium borohydride are added into deoxygenized ultrapure water, a container is sealed and stirred until sodium borohydride is dissolved, then a certain amount of iron salt is added into the container, the container is immediately sealed, the mixture is violently stirred for 30 min, and the mixture is cooled to room temperature to obtain the selenium diselenide / ferroferric oxide heterostructure rich in Se defect. Adding pretreated foamed nickel into the obtained solution, transferring the obtained mixed system into a reaction kettle for hydrothermal reaction, cooling after the reaction is finished, and then washing and drying the foamed nickel to obtain the Se-defect-rich iron diselenide / ferroferric oxide heterostructure attached to a foamed nickel substrate. The FeSe2-x / Fe3O4 (x = 0-1) heterostructure with controllable selenium defect content can be rapidly prepared under mild conditions at low cost, has a good electro-catalysis effect on a nitrate reduction ammonia production reaction, has high activity and selectivity, and is beneficial to rapidly converting nitrate and reducing pollution and harm of the nitrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemistry, and in particular to a preparation method and application of a Se-defect-rich iron diselenide / ferroferric oxide heterostructure. Background Art

[0002] Electrocatalytic nitrate reduction (NO3RR) to ammonia of high application value is a promising denitrification method with the advantages of environmental friendliness, high energy efficiency, and controllable product selectivity. It not only helps to treat industrial pollutants in wastewater but also produces valuable chemicals.

[0003] The nitrate reduction reaction can be divided into the rate-determining step of nitrate conversion to nitrite and the step of nitrite conversion to N2 or NH4. + The selectivity of the step. The nitrate reduction reaction process is not only related to the adsorption of nitrate, but also depends on the number of hydrogen protons provided by hydrolysis and ionization. Especially when the solution is in a neutral environment (C H+ ≤10 -7 M). Therefore, how to quickly convert nitrate while ensuring high selectivity is the key.

[0004] In recent years, transition metal oxides (TMOs), especially iron-based materials, have been widely favored due to their high activity, low cost and environmental friendliness. Fe has disordered three-dimensional orbits, which can easily combine with the extranuclear electrons of O in the NO bond of nitrate, which is conducive to the adsorption and desorption of active groups. 2+ and Fe 3+ The electron transfer between Fe3O4 and Fe3O4 has a unique electronic structure. However, the surface of Fe3O4 lacks suitable active sites for adsorption of *H. The use of iron-based oxide Fe3O4 to prepare a catalyst for catalytic nitrate reduction will be conducive to the rapid conversion of nitrate, thereby reducing the pollution and harm of nitrate. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method and application of a Se-deficient iron diselenide / ferroferric oxide heterostructure, using selenium powder as a selenium source, iron salt as an iron source, and sodium borohydride as a phase transformation and Se defect formation inducer to prepare Se-deficient iron diselenide / ferroferric oxide (FeSe 2-x / Fe3O4, x=0-1, preferably, x=0-0.4, the same below) heterostructure. The method for preparing the FeSe2 / FeO4 heterostructure rich in Se defects by hydrothermal method provided by the present invention can quickly and low-cost obtain FeSe with controllable Se defect content under mild conditions. 2-x / Fe3O4 catalyst, due to the high activity and selectivity of the catalyst, can be well used in the electrocatalytic nitrate reduction reaction.

[0006] The present invention is specifically implemented by the following technical scheme. According to the method for preparing a Se-defect-rich iron diselenide / ferroferric oxide heterostructure proposed by the present invention, the method comprises the following steps:

[0007] (1) Add a certain amount of ultrapure water to a beaker, and then pass argon gas for 30 minutes to remove oxygen in the ultrapure water; add a certain amount of selenium powder and sodium borohydride to the deoxygenated ultrapure water, and then immediately seal the mouth of the beaker with plastic wrap and a rubber band, place it on a magnetic stirrer and stir until the sodium borohydride is dissolved, to obtain solution A; add a certain amount of iron salt to the obtained solution A and immediately seal the mouth of the beaker, and then vigorously stir it on a magnetic stirrer for 30 minutes to obtain solution B;

[0008] In this step, the molar ratio of selenium powder to iron salt is (1.6-1.8):1;

[0009] (2) Add the pretreated nickel foam to the solution B obtained in step (1), and then transfer the obtained mixed system to a polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 180° C. After completion, naturally cool to room temperature, take out the nickel foam and rinse it with ultrapure water and anhydrous ethanol in turn, and then place the nickel foam in a vacuum oven to dry overnight to obtain a Se-defective iron diselenide / iron tetroxide heterostructure attached to the nickel foam substrate.

[0010] Preferably, in step (1), the molar ratio of selenium powder to sodium borohydride is 1:2; and the iron salt is ferric chloride or ferric nitrate.

[0011] Preferably, the size of the pretreated nickel foam in step (2) is 3×3 cm 2 ; The hydrothermal reaction time is 24h.

[0012] The Se-deficient iron diselenide / ferroferric oxide heterostructure obtained according to the aforementioned preparation method has a nano-cubic structure, and nanoparticles are attached to the surface.

[0013] The present invention also provides an application of the Se-deficient iron diselenide / ferroferric oxide heterostructure obtained according to the above preparation method as an electrocatalyst, especially for electrocatalytic nitrate reduction to produce ammonia in a neutral solution. Under the condition of -1.2V vs.RHE, the Se-deficient iron diselenide / ferroferric oxide heterostructure electrocatalytic nitrate reduction has an ammonia yield of 89290 μg h -1 cm -2 , its C dl 0.047mF cm -2 , the selectivity of NH3 is 80.3%.

[0014] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages:

[0015] (1) The present invention uses selenium powder as a selenium source, iron salt as an iron source, and sodium borohydride as a phase transformation and Se defect formation inducer to obtain a Se-defect-rich iron diselenide / iron tetroxide heterostructure through a one-step hydrothermal method. The Se-defect-rich iron diselenide / iron tetroxide heterostructure has a nanocubic structure, and nanoparticles are attached to its surface, and Fe, Se and O elements are evenly distributed on the heterostructure nanosheets.

[0016] (2) The hydrothermal method provided by the present invention for preparing FeSe2 / Fe3O4 heterostructures rich in Se defects can quickly and at low cost obtain FeSe2 / Fe3O4 heterostructures with controllable Se defect content under mild conditions, which has good electrocatalytic effect on nitrate reduction to produce ammonia, and has high activity and selectivity. At -1.2V vs. RHE, FeSe 1.6 The maximum NH3 selectivity of the electrocatalytic nitrate reduction reaction of the / Fe3O4 heterostructure is 80.3%, and the ammonia yield is 89290 μg h -1 cm -2 , and FeSe 1.6 / Fe3O4 heterostructures have good cycling stability for electrocatalytic nitrate reduction to produce ammonia. 1.6 The electrochemically active surface area of ​​the Fe3O4 / Fe3O4 heterostructure is increased, and its catalytic activity in promoting nitrate reduction is enhanced.

[0017] (3) The present invention provides a catalyst with good stability, high activity and high selectivity for the denitrification reaction of nitrate, which is conducive to the rapid conversion of nitrate and reduces the pollution and harm of nitrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The FeSe prepared in Example 1 1.6 Scanning electron microscope (SEM) image (a), transmission electron microscope image (b), high-magnification transmission electron microscope image (c), element distribution map (d), iron element distribution map (e), selenium element distribution map (f) and oxygen element distribution map (g) of the / Fe3O4 heterostructure.

[0019] Figure 2 1 and 2 are XRD diagrams of the heterostructures obtained in Example 1 and Comparative Examples 1-2.

[0020] Figure 3 1 and 2 are Raman images of the heterostructures obtained in Example 1 and Comparative Examples 1-2.

[0021] Figure 4 It is the XPS graph of the heterostructure obtained in Example 1 and Comparative Examples 1-2.

[0022] Figure 5 1 and 2 are EPR diagrams of the heterostructures obtained in Example 1 and Comparative Examples 1-2.

[0023] Figure 6 It is a polarization curve diagram of the electrocatalytic nitrate reduction of the heterostructures obtained in Example 1 and Comparative Examples 1-2.

[0024] Figure 7 Graph showing the ammonia yield of the heterostructures obtained in Example 1 and Comparative Examples 1-2 under different voltages for electrocatalytic nitrate reduction.

[0025] Figure 8 It is a double-layer capacitance diagram of the heterostructure electrocatalytic nitrate reduction obtained in Example 1 and Comparative Examples 1-2.

[0026] Fig. 9 The FeSe obtained in Example 1 1.6 / Fe3O4 heterostructure electrocatalytic nitrate reduction under different voltages H2 / N2 mixed gas, NH3, NO2 - Selective diagram.

[0027] Fig.10 The FeSe obtained in Example 1 1.6 / Fe3O4 heterostructure electrocatalytic nitrate reduction to produce ammonia cycle performance test diagram.

[0028] Fig.11 The FeSe obtained in Example 1 1.6 Ammonia yield at different nitrate concentrations during electrocatalytic nitrate reduction of / Fe3O4 heterostructure.

[0029] Fig.12 The FeSe obtained in Example 1 1.6 / Fe3O4 heterostructures during electrocatalytic nitrate reduction of NO3 at -1.2 V vs. RHE - 、NH3、NO2 - Plot of concentration variation over time. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The present invention is described in detail with specific examples below. If no specific conditions are specified in the following examples, they are all carried out according to conventional conditions or conditions recommended by the manufacturer. The raw materials and reagents used without specifying the manufacturer are all conventional products that can be purchased from the market.

[0032] Embodiment 1:

[0033] (1) In a beaker containing 40 mL of ultrapure water, argon gas was introduced for 30 min to remove oxygen from the ultrapure water. 0.8 mmol of selenium powder and 1.6 mmol of sodium borohydride were added to the deoxygenated ultrapure water. The mouth of the beaker was immediately sealed with plastic wrap and a rubber band. The mixture was placed on a magnetic stirrer and stirred until the sodium borohydride dissolved. Subsequently, 0.5 mmol of ferric chloride hexahydrate was added to the beaker and the mouth of the beaker was immediately sealed with plastic wrap and a rubber band. The solution turned black instantly and was then vigorously stirred on a magnetic stirrer for 30 min.

[0034] (2) Add the pre-treated solution of 3×3 cm to the solution obtained in step (1). 2 The mixed system was then transferred to a polytetrafluoroethylene-lined reactor for hydrothermal reaction at 180 °C for 24 h. After the reaction was completed, the mixture was naturally cooled to room temperature. The nickel foam was taken out and rinsed with ultrapure water and anhydrous ethanol. The nickel foam was then dried in a vacuum oven at 60 °C overnight to obtain FeSe2-rich Se-defects attached to the nickel foam substrate. 1.6 / Fe3O4 heterostructure catalyst.

[0035] The pretreatment operation of the nickel foam is to clean the cut nickel foam with 1M hydrochloric acid, acetone, anhydrous ethanol and ultrapure water in sequence at 70W power for 10 minutes, and then vacuum dry at 60°C for 3-6 hours.

[0036] (I) Se-defect-rich FeSe 1.6 Electrochemical performance test process of / Fe3O4 heterostructure: The dried FeSe 1.6 / Fe3O4 heterostructured nickel foam was laser cut as the working electrode with an area of ​​1×0.5 cm 2 The counter electrode and reference electrode were platinum and saturated calomel electrode, respectively, connected to the Chenhua CHI760e electrochemical workstation, and electrochemical tests were carried out in an H-type electrolytic cell. The cathode electrolyte was a mixed solution containing 0.1M sodium nitrate and 0.5M sodium sulfate, and the anode electrolyte was a 0.5M sodium sulfate solution; before the electrochemical test, Ar gas was passed into the electrolyte for 30min to remove oxygen from the electrolyte, and then CV activation was performed. The polarization curve was in the voltage range of 0 to -1.2V vs. RHE, the scanning speed was 100mV / s, and the data was collected after the scanning current stabilized.

[0037] (ii) Electrocatalytic nitrate reduction reaction (NO3RR): 120 mL of electrolyte was respectively contained in the left and right cells of the H-type electrolytic cell. The cathode electrolyte was a mixed solution of 0.1 M sodium nitrate and 0.5 M sodium sulfate, and the anode electrolyte was a 0.5 M sodium sulfate solution. IT tests were performed at different voltages for 1 h. The yield and selectivity of ammonia and by-products were calculated by UV-visible absorption spectroscopy.

[0038] (III) Determination of NH3 concentration: After the electrocatalytic nitrate reduction reaction (NO3RR) is completed, the NH3 concentration after the NO3RR reaction is determined by the indphenol blue method using the cathode electrolyte. First, 80 μL of the solution is taken out from the cathode chamber of the H-type electrolytic cell and diluted 25 times to 2 mL, and then 2 mL of 1M NaOH solution containing 5wt% salicylic acid and 5wt% sodium citrate is added, and then 1 mL of 0.05M NaClO and 0.2 mL of 1wt% C5FeN6Na2O (disodium nitrosoferricyanide) aqueous solution are added. After reacting in a dark room at room temperature for 2 hours, a UV-visible absorption spectrum test is performed at λ=660nm, and the absorbance obtained by the test is brought into NH4 + The standard curve equation of absorbance versus concentration is multiplied by 25 to obtain the NH3 concentration in the cathode electrolyte after the NO3RR reaction, which is recorded as C NH3 , and then calculate the NH3 yield according to formula (1), and calculate the NH3 selectivity according to formula (2). + The standard curve equation of absorbance versus concentration uses standard NH4Cl solution to test the absorbance of a series of NH4Cl solutions with different concentrations at 660nm (NH4Cl solution concentrations are 0μg mL -1 , 1 μg mL -1 , 2 μg mL -1 , 3 μg mL -1 , 4 μg mL -1 , 5 μg mL -1 , 6 μg mL -1 , 8 μg mL -1 ), with absorbance as the ordinate and NH4Cl concentration as the abscissa, a standard curve of NH4Cl solution absorbance versus concentration was fitted, and the NH4 + The standard curve equation of absorbance versus concentration is: + The standard curve equation is y = 0.05969x + 0.04826, R 2 >0.998.

[0039] NH3 yield calculation formula:

[0040] V NH3 = CNH3 *V / (s*t) (1)

[0041] In formula (1), V NH3 is the NH3 yield, unit: μg h -1 cm -2 ; C NH3 is the NH3 concentration in the electrolyte after the NO3RR reaction, unit: μg mL -1 ; V is the volume of the cathode electrolyte, unit: mL (120 mL in this case); t is the reduction time, unit: h (1 h in this case); s is the surface area of ​​the nickel foam, unit: cm 2 (In this case, 1×0.5cm 2 ).

[0042] NH3 selectivity calculation formula:

[0043] NH3 selectivity = (C NH3 / ΔC NO3 - )×100% (2)

[0044] In formula (2), C NH3 is the NH3 concentration in the cathode electrolyte after the NO3RR reaction, unit: μg mL -1 , ΔC NO3 - =C0-C1, C0 is NO3 in the cathode electrolyte - Initial concentration, unit: μg mL -1 ; C1 is NO3 in the cathode electrolyte after NO3RR reaction - Concentration (calculated as follows), unit: μg mL -1 .

[0045] (IV) NO3 - Concentration determination: After the electrocatalytic nitrate reduction reaction (NO3RR) is completed, the NO3 concentration after the NO3RR reaction is determined using the cathode electrolyte. - First, take out 5 μL of solution from the cathode chamber of the H-type electrolytic cell and dilute it 1000 times to 5 mL, then add 0.1 mL of 1M HCl and 0.01 mL of 0.8 wt.% aminosulfonic acid solution. After standing at room temperature for 10 minutes, use a UV-visible spectrophotometer to measure the absorbance at 220 nm and 275 nm, respectively, using the formula A=A 220nm -2A 275nm Calculation of NO3 - The final absorbance of NO3 - The standard curve equation is calculated and then multiplied by 1000 to obtain NO3 after NO3RR reaction. -Concentration C1. Then calculate NO3 according to formula (3) - Conversion rate. NO3 - The standard curve equation of absorbance versus concentration is: Using NaNO3 standard solution, the absorbance of a series of NaNO3 standard solutions with different concentrations was tested at 220nm and 275nm (the concentrations of NaNO3 standard solutions were 0μgmL -1 , 2 μg mL -1 , 4 μg mL -1 , 6 μg mL -1 , 8 μg mL -1 , 10 μg mL -1 ), with absorbance value A (A=A 220nm -2A 275nm ) as the ordinate and NaNO3 concentration as the abscissa, and the standard curve of NaNO3 solution absorbance versus concentration was fitted to obtain NO3 - The standard curve equation of absorbance versus concentration is: - The standard curve equation is y = 0.05219x-0.00643, R 2 >0.999.

[0046] NO3 - Conversion rate calculation formula:

[0047] NO3 - Conversion rate = (ΔC NO3 - / C0)×100%(3)

[0048] In formula (3), ΔC NO3 - =C0-C1, C0 is NO3 in the cathode electrolyte - Initial concentration, unit: μg mL -1 ; C1 is NO3 in the cathode electrolyte after NO3RR reaction - Concentration, unit: μg mL -1 .

[0049] (V) NO2 - Concentration determination: After the electrocatalytic nitrate reduction reaction (NO3RR) is completed, the NO2 -Concentration. First, take out 50 μL of solution from the cathode chamber of the H-type electrolytic cell and dilute it 100 times to 5 mL, then add 1 mL of color developer (0.4 g of p-aminobenzenesulfonamide), 0.02 g of naphthaleneethylenediamine hydrochloride, 1 mL of phosphoric acid, ρ=1.70 g / mL, and deionized water (5 mL). After reacting in a dark room at room temperature for 20 minutes, perform a UV-visible absorption spectrum test at λ=540 nm. The absorbance obtained from the test is brought into NO2 - The standard curve equation of absorbance versus concentration is calculated and then multiplied by 100 to obtain NO2 after NO3RR reaction. - Concentration C2, and then calculate NO2 according to formula (4) - Selectivity. NO2 - The standard curve equation of absorbance versus concentration is: Using NaNO2 standard solution, the absorbance of a series of NaNO2 standard solutions with different concentrations was tested at 540nm (the concentrations of NaNO2 standard solutions were 0.02μgmL -1 , 0.04 μg mL -1 , 0.08 μg mL -1 , 0.16 μg mL -1 , 0.32 μg mL -1 ), with absorbance as the ordinate, NO2 - Plotting with concentration as the horizontal axis, fitting NO2 - The standard curve of solution absorbance versus concentration was used to obtain NO2 - The standard curve equation of absorbance versus concentration is: - The standard curve equation is y = 0.05992x + 0.0405, R 2 >0.999.

[0050] NO2 - Selectivity calculation formula:

[0051] NO2 - Selectivity = (C2 / ΔC NO3 - )×100%(4)

[0052] In formula (4), C2 is the NO2 in the cathode electrolyte after the NO3RR reaction. - Concentration, unit: μg mL -1 , ΔC NO3 - =C0-C1, C0 is NO3 in the cathode electrolyte - Initial concentration, unit: μg mL -1 ; C1 is NO3 in the cathode electrolyte after NO3RR reaction - Concentration, unit: μg mL -1 .

[0053] (vi) Calculation formula for H2 and N2 gas mixture selectivity;

[0054] H2 and N2 mixture selectivity = ((C0-C1-C2) / ΔC NO3 - )×100%(5)

[0055] In formula (5), C0 is the NO3 in the cathode electrolyte - Initial concentration, unit: μg mL -1 ; C1 is NO3 in the cathode electrolyte after NO3RR reaction - Concentration, unit: μg mL -1 ; C2 is NO2 in the cathode electrolyte after NO3RR reaction - Concentration, unit: μg mL -1 .

[0056] Comparative Example 1:

[0057] (1) In a beaker containing 40 mL of ultrapure water, argon gas was introduced for 30 min to remove oxygen from the ultrapure water; 0.9 mmol of selenium powder and 1.8 mmol of sodium borohydride were added to the deoxygenated ultrapure water, and then the mouth of the beaker was immediately sealed with plastic wrap and a rubber band, and the mixture was placed on a magnetic stirrer and stirred until the sodium borohydride was dissolved; then 0.5 mmol of ferric chloride hexahydrate was added to the beaker, and the mouth of the beaker was immediately sealed with plastic wrap and a rubber band. The solution instantly turned black, and then the mixture was vigorously stirred on a magnetic stirrer for 30 min.

[0058] (2) Add the pre-treated solution of 3×3 cm to the solution obtained in step (1). 2 The mixed system was then transferred to a polytetrafluoroethylene-lined reactor for hydrothermal reaction at 180 °C for 24 h. After the reaction was completed, the mixture was naturally cooled to room temperature, the nickel foam was taken out and rinsed with ultrapure water and anhydrous ethanol in turn, and then the nickel foam was placed in a vacuum oven at 60 °C for overnight drying to obtain FeSe rich in Se defects attached to the nickel foam substrate. 1.8 / Fe3O4 heterostructure catalyst.

[0059] Se-defective FeSe 1.8 The characterization method of the / Fe3O4 heterostructure catalyst, the electrochemical performance testing process, the electrocatalytic nitrate reduction reaction, the testing process and calculation method of the NH3 yield are the same as those in Example 1.

[0060] Comparative Example 2:

[0061] (1) In a beaker containing 40 mL of ultrapure water, argon gas was introduced for 30 min to remove oxygen from the ultrapure water; 1.0 mmol of selenium powder and 2 mmol of sodium borohydride were added to the deoxygenated ultrapure water, and then the mouth of the beaker was immediately sealed with plastic wrap and a rubber band, and the mixture was placed on a magnetic stirrer and stirred until the sodium borohydride dissolved; then 0.5 mmol of ferric chloride hexahydrate was added to the beaker and the mouth of the beaker was immediately sealed with plastic wrap and a rubber band. The solution instantly turned black, and then the mixture was vigorously stirred on a magnetic stirrer for 30 min.

[0062] (2) Add the pre-treated solution of 3×3 cm to the solution obtained in step (1). 2 The nickel foam was then transferred to a polytetrafluoroethylene-lined reactor for a hydrothermal reaction at a temperature of 180°C for 24 hours. After the reaction was completed, it was naturally cooled to room temperature. The nickel foam was taken out and rinsed with ultrapure water and anhydrous ethanol in turn. The nickel foam was then placed in a vacuum oven and dried at 60°C overnight to obtain a FeSe2 / Fe3O4 heterostructure catalyst attached to the nickel foam substrate.

[0063] The characterization method of the FeSe2 / Fe3O4 heterostructure catalyst, the electrochemical performance test process, the electrocatalytic nitrate reduction reaction, the test process and calculation method of the NH3 yield are the same as those in Example 1.

[0064] Figure 1 The FeSe with Se defects prepared in Example 1 of the present invention is 1.6 Scanning electron microscopy (SEM) images (a), transmission electron microscopy (TEM) images (b), high-magnification transmission electron microscopy (HR-TEM) images (c), element distribution (d), iron element distribution (e), selenium element distribution (f), and oxygen element distribution (g) of the Fe3O4 / Fe3O4 heterostructure catalyst. The SEM image (a) shows that the FeSe rich in Se defects 1.6 The / Fe3O4 heterostructure catalyst presents a nanocubic structure with nanoparticles attached to its surface. The lattice spacings of 0.195nm and 0.204nm in the HR-TEM image (c) belong to the (111) and (012) crystal planes of FeSe2, respectively, and the lattice spacings of 0.198nm and 0.239nm belong to the (311) and (400) crystal planes of Fe3O4, respectively, confirming that FeSe 1.6 / Fe3O4 heterostructure. EDS element distribution diagram (d~g) shows that Fe, Se and O elements are 1.6 / Fe3O4 nanosheets are evenly distributed.

[0065] Figure 2The XRD patterns of the heterogeneous structure catalysts prepared in Example 1 and Comparative Examples 1-2 are shown in Figure 1. 35.0° and 36.6° correspond to the (111) and (012) planes of FeSe2, and 35.5° and 43.1° correspond to the (311) and (400) planes of Fe3O4. This indicates that the catalyst prepared in Example 1 is composed of FeSe 1.6 And Fe3O4.

[0066] Figure 3 The Raman graphs of the heterogeneous structure catalysts obtained in Example 1 and Comparative Examples 1-2 are shown in Figure 2. -1 and 565cm -1 The characteristic peaks near 669cm are caused by the vibration between Se-Se or the stretching vibration between them. -1 The Raman pattern is typical of Fe3O4, indicating that Fe3O4 was successfully synthesized on the surface of nickel foam.

[0067] Figure 4 The XPS graphs of the heterogeneous structure catalysts obtained in Example 1 and Comparative Examples 1-2 are shown in Fig. 1.6 The XPS spectrum of / Fe3O4 shows that its structure is composed of Fe, Se, and O. The two main peaks at 712.5 and 723.8 eV are respectively related to Fe 2p 3 / 2 and Fe 2p 1 / 2 Related. FeSe 1.6 / Fe3O4 and FeSe 1.8 In / Fe3O4, the two main peaks of Fe 2p move toward the direction of low binding energy, indicating that the existence of Se vacancies regulates the electronic structure of Fe. The peaks at 54.0eV and 54.9eV are related to selenium, and Se 3d 5 / 2 The peak of Se 3d 3 / 2 The Se-O peak at 57.5 eV indicates that a small amount of selenium is oxidized to SeO x .

[0068] Figure 5 The EPR graphs of the heterogeneous structure catalysts obtained in Example 1 and Comparative Examples 1-2 show that an EPR signal peak is observed at g = 2.004, which is caused by the unpaired electrons captured by the Se vacancy. As the ratio of iron to selenium increases, the EPR signal intensity increases, indicating that the FeSe 1.6 More selenium vacancies are formed on the surface of / Fe3O4.

[0069] Figure 6 The polarization curves of the heterogeneous structure catalysts obtained in Example 1 and Comparative Examples 1-2 for electrocatalytic nitrate reduction with NO3 - Indicates NO3- In the presence of NO3 - Indicates no NO3 - It can be seen that there is NO3 - In the presence of FeSe2 / Fe3O4 and FeSe 1.8 / Fe3O4、FeSe 1.6 / Fe3O4 catalyst has good electrochemical activity and can quickly promote the reduction reaction of nitrate. 1.8 Compared with Fe3O4, FeSe 1.6 / Fe3O4 has a more positive onset potential and a larger current density, indicating that the catalytic activity of the catalyst for promoting nitrate reduction gradually increases with the increase of Se deficiency.

[0070] Figure 7 The ammonia yield of the heterogeneous structure catalysts obtained in Example 1 and Comparative Examples 1 to 2 under different voltages for electrocatalytic nitrate reduction is shown in Figure 1. At -0.8 to -1.2 V vs. RHE, FeSe 1.6 The ammonia yield of the FeSe2 / Fe3O4 heterostructure for electrocatalytic nitrate reduction is higher than that of FeSe2 / Fe3O4 and FeSe 1.8 / Fe3O4, at -1.2V vs.RHE, FeSe 1.6 The ammonia yield of the electrocatalytic nitrate reduction of the / Fe3O4 heterostructure was 89290 μg h -1 cm -2 .

[0071] Figure 8 The double-layer capacitance diagram of the heterogeneous structure catalysts obtained in Example 1 and Comparative Examples 1 to 2 for electrocatalytic nitrate reduction (in the voltage range of -0.1 to 0.3 V vs. RHE, the scan rates are 10 mV / s, 25 mV / s, 50 mV / s, 75 mV / s, and 100 mV / s, respectively). It can be seen that FeSe2 / Fe3O4, FeSe 1.8 / Fe3O4 and FeSe 1.6 / Fe3O4C dl 0.025, 0.038 and 0.047 mF cm respectively -2 .FeSe 1.6 / Fe3O4 has the largest electrochemical active surface area, indicating that FeSe 1.6 / Fe3O4 can provide more active sites for electrochemical reactions.

[0072] Fig. 9The heterogeneous structure catalyst obtained in Example 1 electrocatalyzes nitrate reduction under different voltages for H2 / N2 mixed gas, NH3, NO2 - The selectivity graph shows that the selectivity of NH3 gradually increases with the increase of voltage. At -1.2 V vs. RHE, the selectivity of NH3 is 80.3% at most, while the selectivity of the byproduct nitrite is much lower than that of NH3.

[0073] The FeSe prepared in Example 1 1.6 The / Fe3O4 heterostructure was subjected to 12 electrocatalytic nitrate reduction (NO3RR) tests at a potential of -1.2 V vs. RHE. Each test lasted for 1 h. The ammonia yield after each test was calculated and the ammonia yield was plotted against the number of cycles. Fig.10 As shown in the figure, after 12 consecutive reduction reactions, the ammonia yield fluctuated slightly, indicating that the FeSe prepared in Example 1 1.6 / Fe3O4 heterostructure catalyst has good cyclic stability.

[0074] The initial concentration of nitrate in the cathode electrolyte was changed, and the rest remained unchanged. The FeSe obtained in Example 1 was tested under different initial nitrate concentrations. 1.6 The ammonia yield of the electrocatalytic nitrate reduction of the / Fe3O4 heterostructure is plotted with the ammonia yield as the ordinate and the initial nitrate concentration as the abscissa. The results are shown in Fig.11 As shown in the figure, it can be seen that when the initial nitrate concentration is 500 mM, the ammonia yield is the highest, which is 108310 μg h -1 cm -2 When the nitrate concentration was as low as 10 mM, the ammonia yield was still 10210 μgh -1 cm -2 , indicating that FeSe 1.6 / Fe3O4 heterostructure catalyst has good application potential in treating nitrate wastewater.

[0075] Fig.12 The FeSe obtained in Example 1 1.6 / Fe3O4 heterostructure catalysts for electrocatalytic nitrate reduction of NO3 at -1.2 V vs. RHE - 、NH3、NO2 - The concentration changes over time. It can be seen from the figure that as the reaction time increases, the NH3 concentration gradually increases, and NO3 - The concentration gradually decreased, indicating that nitrate can be effectively converted into ammonia; it takes 54 hours for the nitrate concentration to drop from 100% to 0; in addition, the byproduct NO2 - The concentration of FeSe prepared by the present invention is always maintained at a low level. 1.6 / Fe3O4 heterostructure has a good electrocatalytic effect on nitrate reduction to produce ammonia.

[0076] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a Se-deficient iron diselenide / ferroferric oxide heterostructure, characterized in that: The following steps are involved: (1) introducing argon gas into a certain amount of ultrapure water for 30 minutes to remove oxygen from the ultrapure water; adding a certain amount of selenium powder and sodium borohydride to the deoxygenated ultrapure water, sealing the container and placing it on a magnetic stirrer to stir until the sodium borohydride is dissolved, thereby obtaining solution A; A certain amount of iron salt was added to the obtained solution A and the container was immediately sealed, and then vigorously stirred on a magnetic stirrer for 30 minutes to obtain solution B; In this step, the molar ratio of selenium powder to iron salt is (1.6-1.8):1; (2) Add the pretreated nickel foam to the solution B obtained in step (1), and then transfer the obtained mixed system to a polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 180° C. After the reaction is completed, naturally cool to room temperature, take out the nickel foam and rinse it with ultrapure water and anhydrous ethanol in turn, and then place the nickel foam in a vacuum oven to dry overnight to obtain a Se-defective iron diselenide / iron tetroxide heterostructure attached to the nickel foam substrate.

2. The method for preparing the Se-deficient iron diselenide / ferroferric oxide heterostructure according to claim 1, characterized in that The molar ratio of selenium powder to sodium borohydride in step (1) is 1:

2.

3. The method for preparing the Se-deficient iron diselenide / ferroferric oxide heterostructure according to claim 1, characterized in that: The iron salt described in step (1) is ferric chloride or ferric nitrate.

4. The method for preparing the Se-deficient iron diselenide / ferroferric oxide heterostructure according to claim 1, characterized in that: The size of the pretreated nickel foam in step (2) is 3×3 cm 2 .

5. The method for preparing the Se-deficient iron diselenide / ferroferric oxide heterostructure according to claim 1, characterized in that: The hydrothermal reaction time in step (2) is 24 h.

6. The method for preparing the Se-deficient iron diselenide / ferroferric oxide heterostructure according to claim 1, characterized in that: The obtained Se-deficient FeSe2 / Fe3O4 heterostructures have a nanocubic structure with nanoparticles attached on the surface.

7. Use of the Se-deficient iron diselenide / ferroferric oxide heterostructure obtained by the preparation method of claim 1 as an electrocatalyst.

8. The use according to claim 7, characterized in that The Se-deficient iron diselenide / ferroferric oxide heterostructure is used for electrocatalytic nitrate reduction in neutral solution.

9. The use according to claim 8, characterized in that Electrocatalytic nitrate reduction over Se-deficient FeSe2 / Fe3O4 heterostructures yields 89290 μgh of ammonia at -1.2 V vs. RHE -1 cm -2 , its C dl 0.047mFcm -2 , the selectivity of NH3 is 80.3%.